2013
DOI: 10.1017/jfm.2013.415
|View full text |Cite
|
Sign up to set email alerts
|

Gyrotactic bioconvection at pycnoclines

Abstract: Bioconvection is an important phenomenon in aquatic environments, affecting the spatial distribution of motile micro-organisms and enhancing mixing within the fluid. However, stratification arising from thermal or solutal gradients can play a pivotal role in suppressing the bioconvective flows, leading to the aggregation of micro-organisms and growth of their patchiness. We investigate the combined effects by considering gyrotactic motility where the up-swimming cells are directed by the balance of the viscous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…We could not observe any morphological changes during the experiments, such as resting stages and/or cysts, which could otherwise have stopped the bioconvection pattern due to the immobility of resting stages (Han et al 2002) or led to increased descent/sinking of cysts down below the halocline (Anderson et al 1985). Karimi & Ardekani (2013) applied a continuum model based upon Navier-Stokes equations together with linear stability analysis and large-scale 3-dimensional numerical simulations to foresee how gyrotactic bioconvection could affect spatial distribution of micro organisms in a water column with a constant linear salinity gradient. They concluded that the downwards extension of the bioconvection plume is regulated by the pycnocline.…”
Section: Role Of Bioconvection and Gyrotaxis In Vertical Migrationmentioning
confidence: 85%
See 2 more Smart Citations
“…We could not observe any morphological changes during the experiments, such as resting stages and/or cysts, which could otherwise have stopped the bioconvection pattern due to the immobility of resting stages (Han et al 2002) or led to increased descent/sinking of cysts down below the halocline (Anderson et al 1985). Karimi & Ardekani (2013) applied a continuum model based upon Navier-Stokes equations together with linear stability analysis and large-scale 3-dimensional numerical simulations to foresee how gyrotactic bioconvection could affect spatial distribution of micro organisms in a water column with a constant linear salinity gradient. They concluded that the downwards extension of the bioconvection plume is regulated by the pycnocline.…”
Section: Role Of Bioconvection and Gyrotaxis In Vertical Migrationmentioning
confidence: 85%
“…A prerequisite in this context is that the swimming cells are bottom heavy (like P. reticulatum) and thereby are able to orient themselves by a balance between viscous and gravitational torque (Pedley & Kessler 1992, Karimi & Ardekani 2013, Zhan et al 2014. The viscous torque is due to the vertical shear force formed between the dense falling plume and the upwards swimming cells.…”
Section: Role Of Bioconvection and Gyrotaxis In Vertical Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The collective motion of microorganisms and active colloids has sparked great interest, as biological functions can emerge from self-organisation of local power injection [1][2][3][4][5][6][7][8][9]. To sustain these processes, self-propelled particles increase nutrient uptake [10][11][12][13] and redistribute oxygen [14] by hydrodynamically enhanced mixing [15][16][17], bioconvection [18][19][20], and particle entrainment [21][22][23][24]. The vast majority of these flow-driving swimmers accumulate at surfaces [25][26][27][28][29][30][31][32][33][34][35], at concentrations an order of magnitude larger than in the bulk [25,27,30], and thus form 'active carpets'.…”
mentioning
confidence: 99%
“…. (a) Spatial correlation functions of vertical flows generated by a carpet of bacterial turbulence, gv z (ρ), for heights z ∈[2,20] µm (blue-red). Same asFig.…”
mentioning
confidence: 99%